Child Health in India: An Application of Machine Learning - et. al., Bishweshwar Bhattacharjee, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Child health has a crucial role in the progress of a country like India where more than a tenth of the population are children. As children of today are tomorrow’s citizen, thus it is extremely important to ensure good health for children. This study tried to build an comprehensive state wise child health index compressing various child health indicators namely NNR, IMR and U5MR into ma single indicator through the tool of machine learning. The analysis on CHI indicates that Kerala ranked first while Bihar becomes the worst performing state. On the categorisation of states across regions by various levels of Child Health it emerged that southern region have performed well followed by western region. On the other hand, Northern, eastern and north eastern regions performed poorly. Coming to evaluating a difference between the performance of the states with regard to child health during the span of two NFHS Surveys, there seems to be no significant enhancement in child health index(CHI) during the period as far as conclusion of the t-test is concerned.